Examination of family purchase decision making in the case of some food products - Pólya, Éva (REGIONAL AND BUSINESS STUDIES, 2011)
The role of children within the family is increasing in importance due to the proliferation of one parent families, a lower average in the number of children per family, and the increased rate of families where incomes are higher. Today children have greater independence within the family and experience earlier consumer socialization. In the case of some products, they are well informed, and have a wider knowledge than their parents; hence their role in competency decisions is also growing. Relationships within the family have undergone an appreciable change: children are treated as peers, they are involved in decision making. Shopping is an everyday topic within the family and, as children are well informed and open, shopping questions can be discussed with them. In my paper I take a closer look at the role of children within family decision making and I introduce my research result in this topic. I examined the young and adult population of Hungary to see how families behave when buying certain food products. My aim was to highlight how decisions are made and how participants can influence the process during the different steps.Keywords: family, decision making, food products